Growth, substrate consumption, and product formation kinetics of Phanerochaete chrysosporium and Schizophyllum commune mixed culture under solid-state fermentation of fruit peels - Olorunnisola, Kola Saheed; Jamal, Parveen; Alam, Md Zahangir (Springer Nature, 2018)
Kinetic analysis of solid-state fermentation (SSF) of fruit peels with Phanerochaete chrysosporium and Schizophyllum commune mixed culture was studied in flask and 7 kg capacity reactor. Modified Monod kinetic model suggested by Haldane sufficiently described microbial growth with co-efficient of determination (R2) reaching 0.908 at increased substrate concentration than the classical Monod model (R2 = 0.932). Leudeking–Piret model adequately described product synthesis in non-growth-dependent manner (R2 = 0.989), while substrate consumption by P. chrysosporium and S. commune fungal mixed culture was growth-dependent (R2 = 0.938). Hanes–Woolf model sufficiently represented α-amylase and cellulase enzymes synthesis (R2 = 0.911 and 0.988); α-amylase had enzyme maximum velocity (Vmax) of 25.19 IU/gds/day and rate constant (Km) of 11.55 IU/gds/day, while cellulase enzyme had Vmax of 3.05 IU/gds/day and Km of 57.47 IU/gds/day. Product yield in the reactor increased to 32.65 mg/g/day compared with 28.15 mg/g/day in shake flask. 2.5 cm media thickness was adequate for product formation within a 6 day SSF in the tray reactor.